Kajian Yuridis atas Efektivitas Implementasi Mediasi Elektronik Berdasarkan PERMA No. 3 Tahun 2022 - Adrini, Shaina Subha (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The rapid expansion of e-commerce in Indonesia has intensified the need for a dispute resolution mechanism that is adaptive, efficient, and capable of safeguarding consumer rights within a highly dynamic digital marketplace. While disputes frequently stem from seemingly minor issues, such as; product mismatch, delayed delivery, or service failures. This cumulative impact significantly influences consumer trust in digital transactions. In response, Supreme Court Regulation (PERMA) No. 3 of 2022 introduces electronic mediation as a modern pathway to enhance access to justice. Using a normative legal research method, this study examines the regulatory framework of electronic mediation and its relevance to e-commerce disputes. The findings reveal that although PERMA provides a progressive structure grounded in voluntariness, accessibility, and technological integration, its practical implementation remains constrained by layered administrative requirements, uneven technological infrastructure, limited digital literacy, and the absence of institutional integration between the courts and internal dispute resolution systems offered by e-commerce platforms. These gaps create a misalignment between legal norms and the realities of dispute resolution already functioning within the digital industry. Drawing on comparative insights from Canada’s Civil Resolution Tribunal, this study highlights that effective electronic mediation requires a human-centered, simplified, and integrated justice system.